Stout, Getting The Most Out Of Your U.S. History Course - The History Student’S Guide To History; Whisenhunt, A Student’S Introduction To History - Mugleston, William (Teaching History: A Journal of Methods, 1993)
The problem of new college students not only ignorant of history, but indifferent and even hostile to it, has spawned a sub-industry of "how to" books as supplements to the traditional survey course. These works usually have two aims: to explain to students just what history is (and is not) and to give them practical guidance in navigating their way through a history course-notetaking, reading, coping with exams, producing a research paper, and the like. Here are three of the best.